Evaluating the economic growth of Zhejiang, China: a regional econometric model - Guoping Mao; Hiroyuki Shibusawa; Yoshiro Higano (Penerbit Universiti Kebangsaan Malaysia, 2007)
This article attempts to construct a regional econometric model in Zhejiang province, China, for forecasting its economic growth in the period of 2005 - 2010. The regional economy in Zhejiang province in China is rapidly growing. The regional econometric model which is developed in this paper represents a typical case of the regional economy of a coastal area. Besides forecasting the regional economy of Zhejiang, this article suggests several policy implications for the future regional development of Zhejiang.